The Relationship between Platelet Collagen Receptor Glycoprotein VI and No-Reflow Phenomenon in Patients with Acute ST-Segment Elevation Myocardial Infarction. (January 2014) - Kobat, Mehmet Ali; Balin, Mehmet; Celik, Ahmet; Baydas, Adil; Dagli, Mustafa Necati
Objectives: The purpose of this study was to determine whether admission soluble glycoprotein VI (sGP-VI) level is associated with no-reflow phenomenon (NRP) after primary percutaneous coronary intervention (P-PCI) in patients with acute ST-segment elevation myocardial infarction (STEMI). Methods: A total of 178 consecutive patients admitted to our hospital for a first STEMI and undergoing P-PCI within 12 hours of onset of symptoms were enrolled. The patients were divided into 2 groups (NRP group and reflow group). Admission sGP-VI plasma levels were measured by enzyme-linked immunosorbent assay. Results: Of the 178 patients who underwent P-PCI, 41 patients (23%) developed NRP. The patients in the reflow group had higher levels of sGP-VI compared with the patients in the NRP group (38.5 ± 21.0 vs 21.9 ± 11.9 ng/mL, P < 0.001). The sensitivity and specificity values of the sGP-VI levels were 90% and 49%, respectively (cutoff value was ≤25). In the multivariate logistic regression analyses, sGP-VI levels of 25 ng/mL or lower, higher peak troponin T levels and body mass index value, amount of opaque of greater than 250 mL, and lesion length of greater than 13.5 mm were independent predictors of angiographic NRP. Conclusions: Lower admission sGP-VI levels are associated with NRP in patients with STEMI undergoing P-PCI. This outcome may open new therapeutic facility in the setting of P-PCI.